(untitled) (Itinera, 2024)
The paper is divided into three paragraphs, which explore the aesthetic and poietic nature of habits of thought, highlighting the concurrently sensitive and plural dimensions of their “clothes”. In § 1, the focus is mainly on visual argument studies and visual studies, questioning whether a “logic” of the image must necessarily resolve itself into other than logic. §§ 2-3 delve into the aesthetic-mediological conditions of knowledge production and dissemination, distinguishing between an alphabetic (§ 2) and a “post-alphabetic” (§ 3) phase. § 2 critically examines the issue of “scriptism” ingrained in Western epistemological practices, contending that the linguistic bias within logic reflects a textual bias, according to which the alphabetic-typographic word is deemed the exclusive conduit for rigorous and higher-order knowledge. In contrast, § 3 observes a transformative shift associated with digital media, underscoring the growing importance of the visual in knowledge, and outlining the question of epistemic injustice fuelled by traditional research practices, which tend to sideline visual ways of thinking. The conclusions suggest that as the organa of reason are increasingly “visivizing” or “aestheticizing”, it is at least limiting to remain firm in the belief that this will have no profound impact on the structure of the logos itself.